Exploring halal tourism in Muslim-minority countries: Muslim travellers’ needs and concerns - Said M.F.; Adham K.A.; Muhamad N.S.; Sulaiman S. (Emerald Group Holdings Ltd., 2024)
Indexed by WOS/SCOPUS/ERA